Moving : a memoir of education and social mobility - Hargreaves, Andy (The leading educator series, 2020)
"In Moving: A Memoir of Education and Social Mobility author Andy Hargreaves tells the story of his working-class roots, his education, and his experiences with social mobility. Beginning with his youth in the small working-class town of Accrington in Northern England and ending with his experiences at University, the author relates his journey through the education system and all that education has done for him. The author describes what it means to be working-class, his personal successes and failures, and the ways that education allowed him to lift himself out of poverty. However, he also describes the ways that many others were left behind and never given the chance to be socially mobile. The author believes that there are lessons that can be learned from his experience of social mobility and that these lessons can be applied to society at large. In particular, educators can use these lessons to encourage and support students' social mobility and increase the number of students who can become socially mobile. These lessons can also be used to create schools that are kinder to working-class students and to students who are socially mobile. Readers will connect to the engaging, heart-felt story of the author's life and, through it, learn about the reality of social mobility, how it is experienced, and how it can be supported"--